2012
DOI: 10.1159/000336170
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Proportion of Small, Dense Low-Density Lipoprotein Particles and Lower Adiponectin Blood Levels Predict Early Structural Valve Degeneration of Bioprostheses

Abstract: Objectives: Long-term durability of bioprosthetic heart valves (BPs) are limited by structural valve degeneration (SVD) leading to stenosis and/or regurgitation. In this study, we sought to determine the metabolic markers associated with SVD. Methods: In a cohort of 220 patients with an aortic BP (mean follow-up of 2.5 ± 1.2 years), we compared the metabolic and blood lipid profile including the levels of adiponectin and the proportion of small, dense low-density lipoprotein (LDL) particles (%LDL< Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Also, a high proportion of small, dense LDL has been associated with SVD 14. We also reported that a high apoB/apoA ratio was independently associated with SVD 12.…”
Section: Discussionsupporting
confidence: 53%
“…Also, a high proportion of small, dense LDL has been associated with SVD 14. We also reported that a high apoB/apoA ratio was independently associated with SVD 12.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, 7 of 16 patients with CABG also had DM (Table ). The presence of oxidized low‐density lipoprotein in BHV leaflets with SVD associated hyperlipidemia with SVD, and related lipoprotein abnormalities as comorbidities with SVD leading to BHV reoperation have been observed by others . This may be of importance concerning our observation of increased SVD in CABG patients.…”
Section: Discussionsupporting
confidence: 72%
“…In the study by Shetty et al [29] published in a recent issue of Cardiology , associations were demonstrated between metabolic markers and structural degeneration of bioprostheses in the aortic position. In a population of 220 patients followed for a mean of 2.5 years after valve surgery at a single center in Canada, relatively high (>43.2%) levels of small dense LDL particles were associated with the presence of echocardiographic signs of degeneration of the new bioprosthesis, including increased gradient across the new valve or increased regurgitation when concomitantly low levels of adiponectin (≤1.81 mmol/l) were present, increasing the risk of structural valve degeneration more than 2-fold (odds ratio 2.54, p = 0.04), predominantly for the regurgitation type of valve dysfunction [29].…”
mentioning
confidence: 99%
“…In a population of 220 patients followed for a mean of 2.5 years after valve surgery at a single center in Canada, relatively high (>43.2%) levels of small dense LDL particles were associated with the presence of echocardiographic signs of degeneration of the new bioprosthesis, including increased gradient across the new valve or increased regurgitation when concomitantly low levels of adiponectin (≤1.81 mmol/l) were present, increasing the risk of structural valve degeneration more than 2-fold (odds ratio 2.54, p = 0.04), predominantly for the regurgitation type of valve dysfunction [29]. These findings thus are consistent with previously published data demonstrating that atherosclerotic risk factors and metabolic syndrome predispose to the development of both native aortic stenosis and structural bioprosthesis degeneration, indicating that some common pathogenic mechanisms probably exist between the development of aortic stenosis and bioprosthesis dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation